Tip Post-Grouting of Slurry-Drilled Shafts in Soil: Chinese Experiences - Kulhawy, Fred H; Duan, Xinsheng (Contemporary Topics in Deep Foundations, 2009)
Some Chinese experiences are summarized and evaluated for tip post-grouting of drilled shafts constructed in soil using mud slurry. The factors that affect tip post-grouting are discussed, including many grout issues. Capacity increase is discussed, and some empirical Chinese criteria are cited for increasing the capacity.